Maritime Emergency Management Capabilities in the Arctic - Kheiri Pileh Roud, Ensieh; Borch, Odd Jarl; Jakobsen, Uffe; Marchenko, Nataliya A. (International Society of Offshore and Polar Engineers, 2016)
Author's accepted version (postprint). This is an Accepted Manuscript of an article published by the International Society of Offshore and Polar Engineers in ISOPE - International Society of Offshore and Polar Engineers. Proceedings on 07/2016, available online: http://www.isope.org/publications/proceedings/ISOPE/ISOPE%202016/index.htm